Building Students Cultural Quotient Through Urban Internships and Practica Experiences: In a globalized society, cultural competence may begin at home. - Hough, Tyler (Experiential Learning and Teaching in Higher Education, 2024)
In response to intensified globalization, the importance of Cultural Intelligence (CQ) in U.S. higher education has risen. This study introduces a framework integrating Experiential Learning Theory (ELT) and CQ within an urban, domestic context, challenging the emphasis on international experiences. Using the Chicago Center's immersive programs as a foundation, a new 35-question scale was developed to measure CQ in a domestic setting. Preliminary findings show improved performance across all CQ dimensions, highlighting the efficacy of experiential curricular interventions. This research underscores the need for robust tools in assessing students' CQ development in our globalized society.